Impact of Electromagnetic Field on the Physicochemical Properties, Permeability, and Accumulation of Salicylic Acid - Karolina Zyburtowicz-Ćwiartka; Anna Nowak; Anna Muzykiewicz-Szymańska; Łukasz Kucharski; Maciej Konopacki; Rafał Rakoczy; Paula Ossowicz-Rupniewska (Applied Sciences, 2025)
Transdermal drug delivery offers a non-invasive route for the systemic and localized administration of therapeutics; however, the skin’s barrier function limits its efficiency. This study investigates the application of various electromagnetic field (EMF) configurations to enhance the transdermal delivery of salicylic acid, a model compound with moderate lipophilicity and ionizability. Samples were exposed to pulsed, oscillating, static, and rotating magnetic fields, and their effects on physicochemical properties, thermal stability, skin permeation, and accumulation were evaluated. Structural analyses (FTIR, XRD) and thermal assessments (TGA, DSC) confirmed that EMF exposure did not alter the chemical structure or stability of salicylic acid. In vitro transdermal studies using porcine skin and Franz diffusion cells revealed that pulsed magnetic fields—especially with a 5 s on/5 s off cycle—and rotating magnetic fields at 30–50 Hz significantly enhanced drug permeation compared to controls. In contrast, static fields of negative polarity increased skin retention, suggesting their potential for controlled, localized delivery. These findings demonstrate that EMFs can be used as tunable, non-destructive tools to modulate drug transport across the skin and support their integration into transdermal delivery systems aimed at optimizing therapeutic profiles.